Electroconvulsive therapy in mood diorders - Adhikari, S R (Journal of Chitwan Medical College, 2015)
Electroconvulsive therapy (ECT) is one of the less used somatic treatments in mood disorders, especially depressive phase. ECT use has importance during acute bipolar episode when patient extremely violent, suicidal and extreme psychomotor retardation. The aim of this study was to know about socio-demographic profile and therapeutic efficacy of the use of ECT in mood disorders. Methods: This is a prospective comparative study between patients who received ECT and who did not. Psychopathology was evaluated using Young Mania Rating Scale (YMRS) and Hamilton Depression Rating Scale (HDRS) between the groups at admission, at discharge, at 1st month, at 6th month and at 12th month. Modified ECT was performed using general anesthetic agent. Results: Twenty five patients received ECT as compared to 32 patients who were non-receivers. There was significant decrease in HDRS in ECT receiver as compared to non-receivers in patients with depression (both unipolar and bipolar) at discharge, 1st month, and 12th month; in YMRS in patient with mania at discharge, 1st month and at 12th month. Discussion: There was significant improvement in overall psychopathology and psycho-social status of patients who received ECT as compared to non-receivers. The improvement was shown by decrement in scores in HDRS and YMRS at the time of discharge, 1st month, 6th month and 1st year which were statistically significant. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11958